Elemental characterization and risk assessment of indoor aerosols in an electrostatic particle accelerator laboratory. Issue 1 (1st January 2021) - Reynoso-Cruces, Salvador; Hernández-López, Alfonso Enrique; Miranda, Javier; Mejía-Ponce, Lourdes Verónica
ABSTRACT: Aerosol samples (PM10 and PM2.5 ) were collected during the 2018-2019 dry-cold season, inside an electrostatic particle accelerator laboratory at Instituto de Física, Universidad Nacional Autónoma de México, and on the rooftop. The goal was to measure gravimetric mass and elemental concentrations, to identify emitting sources, and to assess risks to human health due to inhalation, ingestion and dermal deposition, through Hazard Quotients. Concentrations of Mg, Al, Si, P, S, Cl, K, Ca, V, Mn, Fe, Ni, Cu, and Zn were measured with X-ray Fluorescence. Mass concentrations were lower indoors than outdoors. Elemental/gravimetric mass concentrations ratios showed that S, Ni, Cu, and Zn were more abundant in both indoors particle sizes, plus P in PM2.5 . Possible sources, found through Cluster Analysis, were geogenic, SF6 subproducts, vacuum pump oil, and air conditioning, supported by Scanning Emission Microscopy and Electron Probe Microanalysis. Health risks due to enriched elements are not significant.